Liberdade inconstante ou subserviência segura? – O trabalho sexual na Comédia do Cioso - Silva, Carlos (Mulheres no Discurso - Women in Discourse, 2025)
In the “secondary” story of António de Ferreira’s Comédia do Cioso, emerges a confrontation between sex work and matrimonial life. Faustina, a courtesan in-love with Octávio, realizes that the choice for a type of feminine independence granted by sex work means, in the sixteenth century, not only precariousness, but also an irrevocable rejection of love life, that finds its maximum exponent in matrimony. Thus, Clareta, a procurer and Faustina’s friend, disapproves her companion’s passion because she knows that women like them cannot give themselves only to one man. This article aims to understand the literary representation of the Comédia do Cioso’s sex workers, framing it in the sixteenth-century social and cultural vision of sex work.